2015
DOI: 10.1016/j.ophtha.2014.10.014
|View full text |Cite
|
Sign up to set email alerts
|

The Epidemiology of Vitreoretinal Interface Abnormalities as Detected by Spectral-Domain Optical Coherence Tomography

Abstract: Purpose To describe the prevalence and interrelationships of epiretinal membranes, vitreomacular traction, macular cysts, paravascular cysts, lamellar macular holes, full-thickness macular holes, and visual impairment in a population-based study of older adults. Design Cross-sectional study. Participants There were 1913 participants aged 63–102 years at the 20-year Beaver Dam Eye Study follow-up examination in 2008–2010, of whom 1540 (2980 eyes) had gradable spectral-domain optical coherence tomography (SD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
167
3
15

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 213 publications
(196 citation statements)
references
References 30 publications
11
167
3
15
Order By: Relevance
“…However, Meuer et al. (2015) found no significant difference according to sex after adjustment for age. The prevalence was significantly higher with age (1.2% in individuals of 40 to 49 years and 15.5% in individuals of 70 years and older).…”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…However, Meuer et al. (2015) found no significant difference according to sex after adjustment for age. The prevalence was significantly higher with age (1.2% in individuals of 40 to 49 years and 15.5% in individuals of 70 years and older).…”
Section: Discussionmentioning
confidence: 94%
“…The Beaver Dam Eye Study, however, showed a much higher prevalence of 34.1% (Meuer et al. 2015). Both studies confirm an increasing prevalence with increasing age (Mitchell et al.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations